The Correlation Between Motivation and Health Locus of Control with Adherence Dietary of Diabetes Mellitus - Kusnanto Kusnanto; Retno Dwi Susanti; Lailatun Ni'mah; Hakim Zulkarnain (Jurnal Ners, 2018)
Introduction: Controlling blood sugar can be done by dietary adherence of DM. To control glycemic, it is necessary to have motivation and health locus of control to face boredom in dietary adherence of DM. The aim was to analyse the correlation between motivation and health locus of control with dietary adherence of DM.Methods: Cross-sectional design was conducted and involved 106 respondents from five public health centers in Surabaya selected by random sampling. Data were collected by questionnaire Treatment Self-Regulation Questionnaire (TSRQ), Multidimensional Health Locus of Control Scales” (MHLC), and Diet Adherence. The analysis data was using statistical Spearman rho (α ≤ 0.05).Results: There was no correlation between motivation and dietary adherence (p=0.178), and there was a correlation between health locus of control with dietary adherence (p = 0.002).Conclusion: According to analysis, it can be concluded that motivation is influenced by many things to the role the forming of patient behavior in dietary adherence of DM while health locus of control has an influence to dietary adherence of DM. Because of that, it is necessary to increase the factor that influences the behavior of DM control. One of it is health locus of control. So that the glycemic control with dietary adherence of DM can increase and be better.